Subfossil Pollen Spectra in the Altitudinal Belts of the Sikhote-Alin - M. S. Lyashchevskaya; М. С. Лящевская (Izvestiya Rossiiskoi Akademii Nauk. Seriya Geograficheskaya, 2024)
This paper presents the characteristics and comparison of subfossil pollen spectra of modern plant communities in the altitudinal zones of the Northern Sikhote-Alin and the Southern Sikhote-Alin, using the cases of the Tordoki-Yani Mountain (absolute altitude 2090 m) and Oblachnaya Mountain (absolute altitude 1858 m). All pollen spectra from high mountains reflect the forests caused by long-distance transport of tree pollen. Due to the abundance of Picea pollen, the pollen spectra of the mountain tundra and upper part of the subalpine belts of the Northern Sikhote-Alin correspond to the most common type of vegetation at the upper forest borde r-the high-mountain spruce forest with Betula lanata, where Pinus pumila thickets can reach from the overlying belt. The largest amount of allochthonous pollen was found in the pollen spectra on the site without forest canopy. The pollen of broad-leaved trees was brought to high hypsometric levels by mountain-valley winds, rising air currents, from the underlying belts. The quantitative content of pollen of the main dominants of each altitudinal plant zone does not always accurately reflect the role of these taxa in the composition of the communities. The pollen productivity of Betula lanata exceeds the pollen productivity of the main forest forming species in all altitudinal zones, with the exception of the stone birch forests, therefore the share of its participation in the composition of the pollen spectra is overestimated. In the studied pollen spectra the content of Larix pollen is greatly underestimated compared to the role of this species in the forest stand, especially in soil samples from larch forest. It is associated with low pollen productivity, distribution and fossilization characteristics. В данной работе представлена характеристика и проведено сравнение субфоссильных (современных, поверхностных) спорово-пыльцевых спектров (СПС) растительных сообществ высотных поясов Северного и Южного Сихотэ-Алиня, на примере гор Тордоки-Яни (абс. высота 2090 м) и Облачной ...